The brink of poverty: Efficiency and effectiveness of targeted social assistance for poverty reduction in rural China - Lena Kuhn (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2018)
Despite economic growth and extensive development projects, many marginalized Chinese rural households remain trapped in poverty. To safeguard basic livelihood and decrease absolute poverty, the Chinese Rural Minimum Living Standard Scheme (RMLSS) provides income transfers to rural households below an absolute income threshold. For budgetary reasons and incentive considerations, policy makers usually limit the target group and strive for strict exclusion of non-eligible beneficiaries. Political economists however have been disagreeing about the significance of the restrictiveness and accuracy of this so-called targeting for the respective program's anti-poverty effect. The dissertation approaches this question by an in-depth analysis of the impact of narrowly targeted financial transfers on poverty reduction in emerging economies along the example of the Chinese RMLSS. Of interest are the accuracy and effectiveness of the RMLSS transfers, but even more the influence of the targeting method and efficiency in reducing rural absolute poverty. The dissertation focuses on an empirical analysis of the effect of benefit allocation, varying targeting methods, poverty lines and program coverage on poverty reduction of the rural dibao scheme. After the first introductory chapter, the second chapter sets the stage by introducing the social assistances system in question and providing specific background information that is necessary for the later, comprehensive evaluation. In Chapter 3, the major targeting mechanisms are analyzed from a theoretical point of view and contrasted with socioeconomic conditions and policy environment found in the Chinese countryside. [...]
urn:nbn:de:gbv:3:2-106186
Keywords: 330